(3QSGdI ZGjI GdGQJaGY hGdYed HGdHNT GdPi aj BNQ bhS GdGQJaGYs
(3ChdgG (B:s
(3HYO GdHSedg hGdMeO dg (B: (3agP QSGdg SejJgG HZGjI GdGQJaGY hGdYed HGdHNT GdPi ai BNQ bQS GdGQJaGY s
(3BNQgG (B:s
(3hGQLY Edi GdSjfi JLO LjH GdSeJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B10 - (3U(B11s
(3Gdajde ZjQ ehLhOs
(3dGjhLO gPG GdYfhGf ai HQhcdeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B51 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs